Hakikat Menyimak di Kelas Tinggi - Purba, Atikah Zahrani; Lubis, Dicky Chandra; Siregar, Nurhaliza Ertays; Nasution, Juni Sahla (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Language teaching in primary schools plays a key role in developing language skills, including reading, writing, speaking and listening. However, listening skills are often overlooked, even though they are important for understanding and good communication. Listening lessons in elementary school are an important part of learning Indonesian because listening is the functional basis for expressing word symbols to other people. This study uses a literature study method to collect data from various related literature. The results show that advanced listening skills involve understanding complex information and extracting deeper meaning. Advanced listening learning methods include direct, communicative, integrative, thematic, constructivist and contextual methods, each with its own goals and characteristics in developing listening skills. Advanced listening skills are very important for students as they help in understanding subjects and overall development of language skills. Therefore, language teaching in elementary schools must pay attention to the importance of listening skills as an integral part of holistic language learning.d